1992
DOI: 10.1525/maq.1992.6.3.02a00040
|View full text |Cite
|
Sign up to set email alerts
|

What's Wrong with this Picture? The Hegemonic Construction of Culture in AIDS Research in the United States

Abstract: Rather than serving to combat the epidemic, the use of seemingly politically neutral epidemiological categories to portray AIDS risk groups as culturally distinct may have impeded AIDS education and prevention efforts. This article critiques the construction of intravenous drug users (IVDUs) as an AIDS risk group by contrasting the portrayal of an IVDU subculture with studies that report on the diversity of behavior of people who use intravenous drugs. The tendency of epidemiologically oriented AIDS researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 25 publications
0
23
0
5
Order By: Relevance
“…We initially recruited men who self-identified as gay, but during the interviews a significant number of those taking part in the study indicated that they identified more closely with terms like bisexual or homosexual (Mays et al 2004;Operario 2008;Woodyard et al 2000).Taking into consideration these different identities and approaches to sexuality it was not appropriate to refer to all of the men as gay, which is the rationale for our use of the broader, more inclusive term MSM. We understand that the MSM categorization often misses the mark and has clinical connotations that are often problematic because it may fail to reach different sub groups of men (Ford et al 2007;Schiller 1992;Schiller et al 1994). Moreover it is a highly politicized term and may not be how the men refer to one another in their daily lives and within the discourse of the local gay community.…”
Section: Methodsmentioning
confidence: 99%
“…We initially recruited men who self-identified as gay, but during the interviews a significant number of those taking part in the study indicated that they identified more closely with terms like bisexual or homosexual (Mays et al 2004;Operario 2008;Woodyard et al 2000).Taking into consideration these different identities and approaches to sexuality it was not appropriate to refer to all of the men as gay, which is the rationale for our use of the broader, more inclusive term MSM. We understand that the MSM categorization often misses the mark and has clinical connotations that are often problematic because it may fail to reach different sub groups of men (Ford et al 2007;Schiller 1992;Schiller et al 1994). Moreover it is a highly politicized term and may not be how the men refer to one another in their daily lives and within the discourse of the local gay community.…”
Section: Methodsmentioning
confidence: 99%
“…Although the focus of the above approaches is on behavioral characteristics rather than group identity or affiliation, 4 they continue to designate cultural characteristics of target populations; within the context of race and sexual orientation, such research approaches tend to associate black MWSWM in essential ways with HIV/AIDS, treating them monolithically, and positioning them as "other" (Clatts & Mutchler, 1989;Crawford, 1994;Mays & Jackson, 1991;Schiller, 1992;Schiller, Crystal & Lewellen, 1994;Singer, 1990), ultimately reinforcing the marginalizing effects of traditional public health efforts (Brandt, 1988;Jones, 1993).…”
Section: Hlvlaids Prevention Designed For Men Of Color Who Sleep Withmentioning
confidence: 99%
“…Further, government officials are often out of touch with the realities of minority communities, and design policies calling for community response to health crises when those same communities are not provided with the resources to mount such a response (Bayer, 1994;Kaplan, 1990;Roth, 1993). In many instances public health research and campaigns continue to emphasize risk groups in their prevention efforts, a strategy that treats minorities monolithically and maintains their status as other in the culture (Schiller, 1992;Schiller et al, 1994;Wilbain et al, 1994). The consequences of such majority-driven public health efforts are that the messages and the messengers may or may not be culturally sensitive and capable of speaking meaningfully to at-risk communities.…”
Section: Literature Reviewmentioning
confidence: 99%